PENERAPAN MEDIA SCRATCH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV PADA MATERI FOTOSINTESIS - Riki Hidayat, Muhamad; Hadiwijaya Zulkarnaen, Rizki; Maftuh, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted based on the low critical thinking skills of fourth-grade students in the subject of Science and Social Studies (IPAS), particularly on the topic of photosynthesis. The purpose of this study was to improve students' critical thinking skills through the use of Scratch media in the learning process. The research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The study was conducted in two cycles involving 29 fourth-grade students of SDN 3 Cisaruni as the research subjects. Data were collected through observation, critical thinking skill tests, and documentation. The results of the study showed a significant improvement in students' critical thinking skills at each stage of the research. In the pre-action stage, the percentage of students' critical thinking skills was 41.67%, categorized as low. After the implementation of Scratch media in Cycle I, the percentage increased to 51.72%, categorized as fair. Furthermore, in Cycle II, students' critical thinking skills improved to 79.31%, categorized as good. In addition, students' learning outcomes also improved, as indicated by the average scores, which increased from 50% in the pre-action stage to 79.68% in Cycle I and further increased to 84.20% in Cycle II. The findings indicate that the implementation of Scratch media can create a more active, interactive, and enjoyable learning environment, enabling students to better understand the concept of photosynthesis. Therefore, Scratch media is effective in enhancing students' critical thinking skills in IPAS learning.